1998
DOI: 10.1073/pnas.95.2.478
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of GroEL to SecA on the cytoplasmic membrane of Escherichia coli

Abstract: Chaperonin GroEL has been found to interact with isolated cytoplasmic membrane of Escherichia coli. Interaction requires Mg ions, whereas MgATP inhibits, and inhibition is stronger in the presence of co-chaperonin GroES. ''Heat-shock'' of the membrane at 45°C destroys irreversibly its ability to bind GroEL. The binding of GroEL is characterized by saturation with a maximum of about 100 pmol GroEL bound per mg of total membrane protein, indicating a limited capacity and specificity of the membrane to bind GroEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 45 publications
0
30
1
Order By: Relevance
“…We studied the lysis phenomenon of PRD1-infected groE mutant host cells, as the translocation and membrane insertion of holin proteins may be associated with chaperonin activity (5,13,22). E. coli strains carrying mutations in groEL or groES were tested for temperature sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…We studied the lysis phenomenon of PRD1-infected groE mutant host cells, as the translocation and membrane insertion of holin proteins may be associated with chaperonin activity (5,13,22). E. coli strains carrying mutations in groEL or groES were tested for temperature sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was shown that GroEL interacts with SecA, and hence it was suggested that GroEL might be involved in the release of SecA from the membrane (22). Also, DnaK, DnaJ, and GrpE were shown to be involved in the export of a number of SecB-independent proteins, such as alkaline phosphatase, ␤-lactamase, and ribose-binding protein (327,328).…”
Section: Cytosolic Chaperonesmentioning
confidence: 99%
“…A similar phenomenon was observed for another cytosolic molecular chaperone, trigger factor (TF) (18,44). In addition, some of these chaperones are also involved in the specific targeting of the preprotein to Sec translocation sites at the membrane (6,28).…”
Section: Vol 186 2004mentioning
confidence: 53%